2010
DOI: 10.3892/ol_00000039
|View full text |Cite
|
Sign up to set email alerts
|

A comparative histopathological study of systemic candidiasis in association with experimentally induced breast cancer

Abstract: Abstract. systemic candidiasis is a fungal infection which coupled with solid malignancies places patients at high risk of succumbing to the disease. Few studies have shown evidence of the relationship between systemic candidiasis and malignancy-induced immunosuppression disease especially in breast cancer. At present, animal studies that exclusively demonstrate this relationship have yet to be conducted. the exact causative mechanism of systemic candidiasis is currently under much speculation. this study ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Table 2 shows the differentiation of the primary breast tumor as well as lung and liver metastases in each group analyzed using the Kruskal-Wallis test for global comparison of organ metastases among group that was previously described [24]. From the test conducted, we found the p -value to be 0.005 ( p <0.05) for the lungs and liver.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows the differentiation of the primary breast tumor as well as lung and liver metastases in each group analyzed using the Kruskal-Wallis test for global comparison of organ metastases among group that was previously described [24]. From the test conducted, we found the p -value to be 0.005 ( p <0.05) for the lungs and liver.…”
Section: Resultsmentioning
confidence: 99%
“…The images showing the gross morphology of the lungs were captured digitally and the number of tumor nodules on the lungs were counted and recorded in all specimens. The analysis was done using Kruskal-Wallis Test for global comparison of organ metastases among the groups [24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of fungi in the health-care environment has also been implicated in numerous HAI cases. Although aerosolised fungi have been known mainly to cause food spoilage, literature has shown that airborne fungi may result in infectious diseases such as aspergilloses, candidoses, coccidioidomycosis, cryptococcosis, histoplasmosis, mycetomas and paracoccidioidomycosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of systemic candidiasis is the result of an imbalance between pathogen invasion and host defense response. 10 Fungi are recognized by the innate immune system via pattern recognition receptors (PRRs) which are predominantly expressed on myeloid cells, such as Toll-like receptors (TLRs) and C-type lectin receptors (CLRs). 11 Although all of the PRRs are involved in antifungal immune recognition, only CLR pathway mutations are associated with the spontaneous human fungal infections development.…”
Section: Introductionmentioning
confidence: 99%